Development of navigation system for unmanned surface vehicle by improving path tracking performance - Putri Nur Farhanah, Mohd Shamsuddin; Muhamad Arifpin, Mansor; Roshahliza, M. Ramli; Raja Mariatul Qibtiah, Raja Jaapar (Taylor's University, 2020)
A fundamental of a fully unmanned vehicle entails the use of Global Positioning System (GPS) and sensors module that emits USV a series of a waypoint for moving towards the target. In other words, GPS provides an accurate data location longitude and latitude for monitoring purposes. However, this real-time tracking path needs to extend their application for moving in curvature motion. Based on this fact, the real-time autonomous navigation system of USV will improve in this research by implementing the mathematical equation that will communicate with the GPS sensor. The objectives of this project are developing a navigation system that will determine a real-time of an unknown target location by using GPS and focuses on validating an ability of mathematical equation for correcting the error occurred between USV heading and the target heading error path. In this project, the system is divided into two parts; target platform and USV platform. Target platform is left freely on the water surface with an unknown location. RF Transceiver module 2 in the USV platform receives the information signal from RF Transceiver module 1 in the target platform. Employment of the PP Guidance controller will be engrossed in this project for estimating the future goal point by computing the goal point coordinate and the current USV body commands. Hence, the distance between two coordinates has been computed in the controller for getting new coordinates as a new waypoint towards the Target platform. Based on this experiment, there is some error occurred due to the sensors on-board. For further research, USV platform needs to add a PID controller to overcome the interruption reading between mathematical equation heading routing to get the actual result.